Dynamic Satellite Seascapes as a Biogeographic Framework for Understanding Phytoplankton Assemblages in the Florida Keys National Marine Sanctuary, United States - Montes, Enrique; Djurhuus, Anni; Muller-Karger, Frank E.; Otis, Daniel; Kelble, Christopher R.; Kavanaugh, Maria T. (Frontiers in Marine Science, 2020)
Physical, chemical, geological, and biological factors interact in marine environments to shape complex but recurrent patterns of organization of life on multiple spatial and temporal scales. These factors define biogeographic regions in surface waters that we refer to as seascapes. We characterize seascapes for the Florida Keys National Marine Sanctuary (FKNMS) and southwest Florida shelf nearshore environment using multivariate satellite and in situ measurements of Essential Ocean Variables (EOVs) and Essential Biodiversity Variables (EBVs). The study focuses on three periods that cover separate oceanographic expeditions (March 11-18, May 9-13, and September 12-19, 2016). We collected observations on bio-optical parameters (particulate and dissolved spectral absorption coefficients), phytoplankton community composition, and hydrography from a ship. Phytoplankton community composition was evaluated using 1) chemotaxonomic analysis (CHEMTAX) based on high-performance liquid chromatography (HPLC) pigment measurements, and 2) analysis of spectral phytoplankton absorption coefficients (aphy). Dynamic seascapes were derived by combining satellite time series of sea surface temperature, chlorophyll-a concentration, and normalized fluorescent line height (nFLH) using a supervised thematic classification. The seascapes identified areas of different salinity and nutrient concentrations where different phytoplankton communities were present as determined by hierarchical cluster analyses of HPLC pigments and aphy spectra. Oligotrophic, Mesotrophic and Transition seascape classes of deeper offshore waters were dominated by small phytoplankton (< 2 µm; ~ 40-60 % of total cell abundance). In eutrophic, optically shallow coastal seascapes influenced by fresh water discharge, the phytoplankton was dominated by larger taxa (> 60 %). Spectral analysis of aphy indicated higher absorption levels at 492 and 550 nm wavelengths in seascapes carrying predominantly small phytoplankton than in classes dominated by larger taxa. Seascapes carrying large phytoplankton showed absorption peaks at the 673 nm wavelength. The seascape framework promises to be a tool to detect different biogeographic domains quickly, providing information about the changing environmental conditions experienced by coral reef organisms including coral, sponges, fish and higher trophic levels. The effort illustrates best practices developed under the Marine Biodiversity Observation Network (MBON) demonstration project, in collaboration with the South Florida Ecosystem Restoration Research (SFER) project managed by the Atlantic Oceanographic and Meteorological Laboratory of NOAA (AOML-NOAA).